Virtual Care: A Concept Analysis - Kurniawan, Moh Heri; Rustina, Yeni; Nuraini, Tuti; Handiyani, Hanny (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
The concept of virtual care has not been consistently defined for its use in healthcare. Overall, the definition of virtual care available is in the form of the use of communication technology with the aim of providing health services. This study aims to clarify the concept of virtual care. Walker and Avant concept analysis methods were used in this study. Literature searches were also conducted from four databases: PubMed, CINAHL, and Scopus, and Google Scholar, to find articles until July 2022. The literature search obtained 14 articles on virtual treatment from different disciplines.  Four attributes were developed from the concept analysis, including 1) remote health care delivery, interaction between patients and health workers, 2) communication between patients and health workers, 3) communication using audio, visual, and short message-based technology, Asynchronous, 4) aiming to improve access, effectiveness, and efficiency of services. Two types of antecedents were identified in the concept of virtual care related to virtual care needs involving factors such as use cases, payment barriers, regulatory changes, and technology, as well as antecedents from virtual care, namely conventional face-to-face consultations and considering physical or geographical constraints. In addition, it was found to be in the form of increased service effectiveness, service efficiency, and cost reduction. Conclusion: Concept analysis provides four comprehensive attributes, antecedents as well as consequence. However, this concept can be used to provide nursing care remotely, assessing the provision of remote nursing care